La letteratura orale embera: inquietudini e oscillazioni enunciative nel mito contemporaneo - Simone Ferrari (Confluenze)
Starting from a redefinition of the notion of 'oral literature', this essay analyzes two versions of the myth of Jinu Potó, narrated by two members of the Embera community in Colombia. The analysis weaves together a study of the motifs with an exploration of what occurs between the act of narration. According to the thesis proposed, what happens in the course of storytelling complements the textual dimension of oral literature, condensing traces of the epistemic reconfiguration process taking place in contexts of forced displacement.